2000
DOI: 10.1038/sj.bjp.0703522
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prostanoid receptors mediating actions of the isoprostanes, 8‐iso‐PGE2 and 8‐iso‐PGF, in some isolated smooth muscle preparations

Abstract: 1 We investigated the contracting actions of the isoprostanes (isoPs), 8-iso-prostaglandin (PG) F 2a and 8-iso-PGE 2 , in comparison to the eects of the thromboxane (TX) A 2 -mimetic U 46619 and the traditional prostaglandin PGE 2 in the isolated rat aorta, isolated rat gastric fundus and the isolated guinea-pig ileum. 2 U 46619 and 8-iso-PGF 2a caused contractions in the rat aorta and rat gastric fundus in a concentration-dependent manner, whereas these agonists showed no eects in the guinea-pig ileum. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Other reports have suggested that, in the presence of oxidative damage, PG could be converted into products of oxidation, such as 8-iso-PGF 2a (Natale et al 2004), that induce vasoconstriction and platelet aggregation that might enhance ulcerogenic actions of necrotizing agent and promote tissue oxidation (Sametz et al 2000). The effect of fluoxetine on gastric acid secretion and subsequently higher gastric pH compared to values in the untreated ulcer counterparts may be secondary to its effect on NO and COX enzymes.…”
Section: Discussionmentioning
confidence: 97%
“…Other reports have suggested that, in the presence of oxidative damage, PG could be converted into products of oxidation, such as 8-iso-PGF 2a (Natale et al 2004), that induce vasoconstriction and platelet aggregation that might enhance ulcerogenic actions of necrotizing agent and promote tissue oxidation (Sametz et al 2000). The effect of fluoxetine on gastric acid secretion and subsequently higher gastric pH compared to values in the untreated ulcer counterparts may be secondary to its effect on NO and COX enzymes.…”
Section: Discussionmentioning
confidence: 97%
“…Since it has been established that stimulation of prostanoid receptors caused contraction in the guinea pig ileum (34), prostaglandin-like compounds may be involved in [6]-gingerol-induced contraction. However, [6]-gingerol is reported to be an inhibitor of prostaglandin synthetase and 5-lipoxygenase in vitro (35,36).…”
Section: Involvement Of Nk 1 Receptors and Prostaglandins Formation Omentioning
confidence: 99%
“…Isoprostane 8-iso-PGF 2␣ appears to act through the thromboxane-selective TP prostanoid receptor to induce vasoconstriction (13,17) and bronchoconstriction (25). Some studies indicate that 8-iso-PGE 2 may act similarly on the TP receptor (12,(22)(23)(24)42), whereas others indicate the involvement of FP and EP prostanoid receptors in mediating the excitatory activity of 8-iso-PGE 2 (40,44). Inhibitory activity is also observed for the isoprostanes (8,22), with 8-iso-PGE 2 seemingly acting at the inhibitory EP receptors to induce airway relaxation (8).…”
mentioning
confidence: 99%